Teacher's attitudes towards inclusion and burnout in Republic of Srpska: Pilot study - Subotić, Siniša (Primenjena psihologija, 2010)
This study, following the assumption of stressfulness of inclusion reform on teachers, addressed two questions: the structure of teacher’s attitudes towards inclusion in The Republic of Srpska, and the relationship of these attitudes with teacher’s burnout. The study comprised 115 teachers from 11 elementary schools from Prijedor region of The Republic of Srpska. Based on the results of two previous focus groups, an Attitude towards Inclusion Questionnaire – SINKL was constructed. After eliminating poor metric characteristics items, total of 27 items remained in the final version of the questionnaire, organized in 3 Promax factors (explaining 37.94% shared variance): Partial inclusion, Acceptance and adaptedness, and Cooperation and support. All scales had good psychometric properties. Relationship with burnout was investigated using a linear regression analysis. Independent variables were 3 SINKL factors, 5 personality traits and Infrequency score messured by Zuckerman-Kuhlman Personality Questionnaire, and a number of disabled students that teacher works with. Dependant variable was a burnout score, measured by 20-item Teacher Burnout Scale. The obtained regression model of moderate effect strength was statistically significant (R2 = .211, p<.01), with SINKL factor Acceptance and adaptedness as a neagtive, and Neuroticism / Anxiety as a positive partial predictor of burnout levels, thus confirming the existance of a relationship between working in an inclusive classroom and perceived teacher’s distress. These results suggest the importance of examining the underlying mechanisms responsible for this relationship, in order to mitigate negative effects, and improve the school process as a whole.